Food process engineering : safety assurance and complements - Malcata, F. Xavier (Boca Raton, FL : CRC Press, 2020)
"Food Process Engineering : Safety Assurance and Complements pursues a logical sequence of coverage of industrial processing of food and raw material where safety and complementary issues are germane. A brief overview of useful mathematical tools from algebra, calculus, and statistics is conveyed for convenience as Appendix"--
OCLC-licensed vendor bibliographic record.
Keywords: Food -- Preservation; Food -- Safety measures; Cooking; Food service -- Sanitation; TECHNOLOGY / Food Science